Pelaksanaan Peraturan Gubernur Nomor 24 Tahun 2012 Tentang Petunjuk Pkb Dan Bbn-Kb Di Kantor Pelayanan Pajak Daerah Tanjungpinang - Lili Rasjidi; Rina Shahriyani Shahrullah; Riza Satya Putri (Journal of Judicial Review, 2017)
This study was intended as a form of submission of information and accountability to the public as compliance with the principles of transparency and accountability for public service in call centers Tanjungpinang. The goal is to keep the public information on the public service call centers that have been developed. With the increasing awareness of the community, also increasing the financial resources to fund programs and projects the Development of public facilities in order to boost the welfare masrakat Riau Islands.